Achievements and Challenges of Iran Health System after Islamic Revolution: Structural reforms at the second step - Mohammad Meskarpour-Amiri; Mohammad Karim Bahadori; Seyed Mostafa Hakimzadeh (ACHSM, 2021)
This commentary explained the causes of health financing issues in IRAN and needs for a structural reforms in the near future.